Human resources model based on Islamic values in sharia banking / Popy Novita Pasaribu ... [et. al] - Pasaribu, Popy Novita; Hubeis, Musa; Sa’id, E. Gumbira; Hermawan, Aji (2011)
The objective of this study was to find out the model of human resources (HR) based on Islamic values. This study took place in sharia banking in Indonesia which were Bank Muamalat Indonesia (BMI) and BNI Syariah. Data analysis used for this study was Stuctural Equation Modeling (SEM) technique. Islamic values had significant and positive effect on the meaning of prayer, corporate culture, job satisfaction and organization commitment. Concentration, understanding, respect, fear and admiration, indicated the meaning of prayer that were valid and reliable provided a significant contribution directly to the formation of corporate culture, job satisfaction and organization commitment. The corporate culture had significant and positive impact on job satisfaction and organization commitment. Job satiscation gave positive and significant influence towards organization commitment. Result of comparative analysis showed that at BMI Islamic values significantly influenced the other four variables, likewise the other relations. Whilst BNI Syariah, meaning of prayer did not influence significantly corparate culture and job satisfaction did not give considerable affect on organization commitment.